LEANING OUT;A FAIRER FUTURE FOR WOMEN AT WORK IN AUSTRALIA. - KRISTINE ZIWICA (HARDIE GRANT BOOKS, 2022)
From Lean In-style feminism to the Great Resignation, this book deconstructs the recent history of Australian women at work and plots a collective path forward.
Keywords: Women -- Employment -- Australia.; Sex discrimination against women -- Australia.; Sex discrimination in employment -- Australia.; Discrimination à l'égard des femmes -- Australie.; Discrimination sexuelle dans l'emploi -- Australie.; Labor.; BUSINESS & ECONOMICS.; Workplace Culture.; Feminism & Feminist Theory.; SOCIAL SCIENCE.; Sex discrimination against women; Sex discrimination in employment; Women -- Employment; Australia